Combining a Phenanthroline Moiety with Two Peralkylated Guanidine Residues: Janus Head Pro‐Ligands. Issue 40 (30th October 2017) - Ortmeyer, Jochen; Vukadinovic, Yannik; Neuba, Adam; Egold, Hans; Flörke, Ulrich; Henkel, Gerald
Abstract : A novel family of Janus head pro‐ligands is described that combine a phenanthroline moiety with two peralkylated guanidine residues. The bis‐bidentate molecules provide coordination sites with metal‐differentiating properties and thus are especially well suited to form heterobinuclear complexes. Synthesized members of this family differ in their substitution patterns and comprise variants with tetramethyl‐, tetraethyl‐, dipentylene‐, dimethylethylene‐, and dimethylpropylene‐guanidino functionalities. They were characterized by low‐temperature X‐ray crystallography and studied by means of temperature‐dependent 1 H NMR spectroscopy, which provided information on the dynamics of their guanidine moieties. Furthermore, the redox behavior was investigated by using cyclic voltammetric techniques. Abstract : Combing a phenanthroline moiety with two peralkylated guanidine residues leads to a novel family of Janus head pro‐ligands with site‐specific metal‐differentiating properties. The ligands differ in the substitution pattern of their peralkylated guanidine functionalities. They were characterized by X‐ray crystallography, temperature‐dependent 1 H NMR spectroscopy and cyclic voltammetric techniques.